Identification of the relationship between coat color and growth performances in Menz sheep - CGIAR Research Program on Livestock (2020)
The relationship between coat color and growth performance is established. The next step will be to pilot use of these findings with stakeholders in the Menz sheep community based breeding program, taking them into account in breeding objectives and tackling the cultural norms about not keeping black animals.